Normal saline versus balanced crystalloids in patients with prerenal acute kidney injury and pre-existing chronic kidney disease - Papasotiriou Marios; Mpratsiakou Adamantia; Georgopoulou Georgia; Ntrinias Theodoros; Balta Lamprini; Pavlakou Paraskevi; Goumenos Dimitrios S.; Papachristou Evangelos (Sciendo, 2023)
Normal saline (N/S) and Ringer's-Lactate (L/R), are administered in everyday clinical practice. Despite that, N/S increases the risk of sodium overload and hyperchloremic metabolic acidosis. In contrast, L/R has lower sodium content, significantly less chloride and contains lactates. In this study we compare the efficacy of L/R versus N/S administration in patients with prerenal acute kidney injury (AKI) and pre-established chronic kidney disease (CKD).